Parametric study of laser engraving process of AISI 304 Stainless Steel by utilizing fiber laser system - Mohd Noor Firdaus, Haron; F. R. M., Romlay (IOP Publishing, 2019)
Laser engraving process is non-conventional machining process used for engraving of almost each material which cannot be mark by conventional machining processes. Laser engraving process is done by heat up mechanism which vaporize the material surface. With the use of laser engraving machine the engraving is possible by utilizing different input parameter as spot diameter, laser power, laser frequency, different wave length, engraving speed, number of passes etc. Output parameter is potentially material removal rate, surface finish and indentation. Parameters with multiple responses characteristic is optimized based on the Taguchi method analysis. Three input parameter (frequency, engraving speed and number of passes) were investigated its effect on surface roughness as it output parameter.